2019
DOI: 10.1037/xlm0000584
|View full text |Cite
|
Sign up to set email alerts
|

Persistent structural priming during online second-language comprehension.

Abstract: We report 2 self-paced reading experiments investigating the longevity of structural priming effects in comprehending reduced relative clauses among adult Chinese-speaking learners of English. Experiment 1 showed that structural priming occurred both when prime and target sentences were immediately adjacent and when they were separated by 1 or 2 filler sentences of unrelated structures. Moreover, the magnitude of the priming effect held constant across different lag conditions. Experiment 2 replicated the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The extent to which priming is lexically mediated in L2 processing is however debated. Some studies have shown lexically independent structural priming during comprehension (e.g., Nitschke et al, 2014;Wei et al, 2019), while others suggest lexically mediated structural priming (e.g., Wei et al, 2018). Thus, as also found in L1 studies of priming during comprehension discussed above, priming during comprehension in L2 speakers appears stronger in the presence of lexical overlap.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…The extent to which priming is lexically mediated in L2 processing is however debated. Some studies have shown lexically independent structural priming during comprehension (e.g., Nitschke et al, 2014;Wei et al, 2019), while others suggest lexically mediated structural priming (e.g., Wei et al, 2018). Thus, as also found in L1 studies of priming during comprehension discussed above, priming during comprehension in L2 speakers appears stronger in the presence of lexical overlap.…”
mentioning
confidence: 57%
“…Most importantly for present purposes, L2 participants showed that unambiguous but not ambiguous prime sentences facilitated processing of the globally correct interpretation of ambiguous target sentences, as also found in L1 participants. This suggests that the structural representation that L2 speakers create during online reading is stable enough to cause priming effects during language comprehension (Nitschke et al, 2010(Nitschke et al, , 2014Wei et al, 2019).…”
Section: Reanalysis In L2 Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, researchers are interested in the relationship between multilingualism and second/additional language acquisition. For example, researchers are interested in how the language information of a bilingual or multilingual is represented and processed in the mind [18][19][20][21][22]. In addition, people have investigated how the languages are acquired or learned [23][24][25][26] or attritted or lost [27][28][29].…”
Section: Introductionmentioning
confidence: 99%